Weighed and Wanting: Addresses on the Ten Commandments - Moody, Dwight Lyman, 1837-1899 (Salt Lake City, UT : Project Gutenberg, 2010)
"Weighed and Wanting: Addresses on the Ten Commandments" by Dwight Lyman Moody is a religious work written in the late 19th century. The book focuses on the examination and interpretation of the Ten Commandments, presenting them as fundamental moral laws that govern human conduct and relationships with God and each other. Moody's aim is to emphasize the lasting relevance of these commandments and challenge readers to evaluate their adherence to these divine principles. At the start of the book, Moody introduces the theme of divine judgment, drawing on the biblical narrative of King Belshazzar's feast. He describes how Belshazzar's impious actions lead to his sudden demise, serving as a dire warning about the consequences of ignoring God's commandments. The opening sets the tone for Moody's exhortation to his audience, urging them to consider their standing in relation to God's law and adhere to the Ten Commandments with sincerity. He stresses the importance of self-reflection and the readiness to be "weighed" against these divine standards, driving home the point that obedience to God's commandments is crucial for spiritual integrity and salvation. (This is an automatically generated summary.)
Release date is 2010-08-03
Produced by Keith G Richardson
Keywords: Sermons, American; Ten commandments -- Sermons